Job satisfaction and organizational climate as mediators in the relationship between internal social responsibility and organizational commitment - Licandro, Oscar (Estudios de Administración, 2022)
Different research have found a positive relationship between Internal Social Responsibility and the organizational commitment of employees, but the possible participation of other variables that mediate in this relationship needs to be studied in greater depth. The purpose of this paper is to assess whether this relationship is mediated by two widely studied factors in organizational management: employee satisfaction and the organizational climate. Information provided by a non-probabilistic sample of companies that have incorporated Social Responsibility into their operations in Uruguay was analyzed. A questionnaire was used that includes indicators on: specific Internal Social Responsibility practices, three dimensions of organizational commitment (identification, engagement and membership) and the two control variables (job satisfaction and organizational climate). It was found that Internal Social Responsibility correlates positively with two aspects of organizational commitment (identification and engagement), that this relationship is independent of the two control variables in the case of identification, but that it is mediated by them in the case of engagement. These results suggest that the relationship between Social Responsibility and organizational commitment is complex and that other factors intervene, therefore, in research and management, the role of these factors should be taken into account.